Determinants of Quick Response Code Indonesian Standard Usage and its Impact on Impulsive Buying Behaviour Among Indonesian Consumers - Ramayanti, Rizka (2024)
QRIS is a new phenomenon in the payment industry in Indonesia. QRIS has increased in terms of the number of transactions and in Rupiah. However, the QRIS system does not work well in traditional markets. To examine these phenomena, this study aims to examine the determinants of QRIS usage and its impact on the impulse buying behaviour of Indonesian consumers. Using the unified theory of acceptance and use of technology (UTAUT2) model with the addition of independent variables comprising compatibility, personal innovativeness, and cost from Diffusion of Innovation (DIT) theory and dependent variable comprising impulsive buying behaviour from Stimulus-Organism-Response (SOM) theory. Using a questionnaire survey, this study sampled 781 QRIS users in Jakarta, Indonesia, as respondents. The primary data collected was analyzed using SmartPLS 4.0 software. The research findings show that social influence, price value, habit, compatibility, personal innovativeness, and cost are the main factors that influence the use of QRIS in Jakarta, Indonesia. Unlike prior research in the body of knowledge that primarily concentrated on QRIS adoption factors, this study extends a step further by exploring the effect or influence of QRIS adoption on customer behaviour, particularly impulsive buying behaviour, and has shown significant results. The results of this study can help the government in developing marketing campaigns and promotional materials that encourage customers to take advantage of QRIS. It can help future researchers understand the use of the UTAUT2 development model with additional variables of compatibility, personal innovativeness and cost in analysing the use of QR codes and their influence on impulsive buying behaviour in other developing countries with socio-economic characteristics similar to Indonesia.